Manganese Toxicity Inhibited Root Growth by Disrupting Auxin Biosynthesis and Transport in Arabidopsis - Zhao, Jingjing; Wang, Wenying; Zhou, Huakun; Wang, Ruling; Zhang, Ping; Wang, Huichun; Pan, Xiangliang; Xu, Jin (Frontiers in Plant Science, 2017)
Mn toxicity inhibits both primary root (PR) growth and lateral root (LR) development. However, the mechanism underlying Mn-mediated root growth inhibition remains to be further elucidated. Here, we investigated the role of auxin in Mn-mediated inhibition of PR growth in Arabidopsis using physiological and genetic approaches. Mn toxicity inhibits PR elongation by reducing meristematic cell division potential. Mn toxicity also reduced auxin levels in root tips by reducing IAA biosynthesis and down-regulating the expression of auxin efflux carriers PIN4 and PIN7. Loss of function pin4 and pin7 mutants showed less inhibition of root growth than col-0 seedlings. These results indicated that this inhibitory effect of Mn toxicity on PR growth was mediated by affecting auxin biosynthesis and the expression of auxin efflux transporters PIN4 and PIN7.